2021 IEEE Virtual Reality and 3D User Interfaces (VR) 2021
DOI: 10.1109/vr50410.2021.00095
|View full text |Cite
|
Sign up to set email alerts
|

Who Are Virtual Reality Headset Owners? A Survey and Comparison of Headset Owners and Non-Owners

Abstract: The number of people who own a virtual reality (VR) head-mounted display (HMD) has reached a point where researchers can readily recruit HMD owners to participate remotely using their own equipment. However, HMD owners recruited online may differ from the university community members who typically participate in VR research. HMD owners (n=220) and non-owners (n=282) were recruited through two online work sites-Amazon's Mechanical Turk and Prolific-and an undergraduate participant pool. Participants completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
(41 reference statements)
5
23
1
Order By: Relevance
“…Comparing our sample to the subset of crowdworkers who are HMD-owners shows a similar biased representation. Kelly et al (2021) recently conducted a survey of headset owners and non-owners in online platforms (AMT and Prolific), comparing an undergraduate participant pool, also showed a negligible proportion of women and elders among HMD owners. Naturally, this imposes some limitations on studies conducted this way; specifically with regard to generalizability of findings.…”
Section: Samplementioning
confidence: 99%
“…Comparing our sample to the subset of crowdworkers who are HMD-owners shows a similar biased representation. Kelly et al (2021) recently conducted a survey of headset owners and non-owners in online platforms (AMT and Prolific), comparing an undergraduate participant pool, also showed a negligible proportion of women and elders among HMD owners. Naturally, this imposes some limitations on studies conducted this way; specifically with regard to generalizability of findings.…”
Section: Samplementioning
confidence: 99%
“…One notable difference between remote VR studies and lab-based studies is the shift in participant demographics. A survey comparing VR headset owners to non-owners [10] reported that women are underrepresented among VR owners. Underrepresentation of women has been documented even in lab-based VR research [22], and this problem is likely to be compounded in remote VR research that recruits VR owners.…”
Section: Remote Vr Researchmentioning
confidence: 99%
“…In one recent and relatively large (n=226) remote VR study [17], women comprised only 12% of the final sample. Another potentially important sample difference is that VR headset owners, on average, spend more time playing video games than do non-owners [10]. Demographic differences such as these are particularly relevant to VR research due to 1) the inherently spatial nature of VR and 2) the documented associations between spatial ability and participant characteristics such as gender and video game experience [6,10].…”
Section: Remote Vr Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing number of HMD owners now allows us to conduct our VR research remotely. Since research has shown that there is no significant difference between HMD owners recruited online, in university laboratories or with AMT 1 , except for the number of hours played by female owners (Kelly, J. W., et al, 2021). We have chosen to recruit our HMD owners and our control group via social networks, on public and private specialized groups.…”
Section: Online Processmentioning
confidence: 99%